Estimating the potential to close yield gaps through increased efficiency of chickpea production in Ethiopia - Kumar, Shalander; Das, Abhishek; Hauser, Michael; Muricho, Geoffrey; Degefu, Tulu; Fikre, Asnake; Ojiewo, Christopher Ochieng; Ferede, Setotaw; Varshney, Rajeev K. (Springer, 2022)
Improved cultivars and agronomic practices have significantly increased chickpea production in Ethiopia in recent decades. Enhanced availability of chickpeas in Ethiopia, therefore, contributes to food, nutrition, and income security of the country. However, we know relatively little about the extent to which farmers have harnessed the full potential of these improved technologies. In this paper, we compare the technical efficiencies and technological gap ratios of chickpea farming in three major chickpea-producing areas of Ethiopia using a two-step meta frontier model. Based on regionally representative data from 681 chickpea-growing farm households in the three regions, we show regional differences in the technical efficiencies, technological gap ratios, and meta technical efficiencies (MTEs). We examined the drivers of these different production levels and identified ways to increase chickpea production while minimizing yield gaps. Improving technical efficiency through improving farmers’ access to improved seed, offering farmers need-based and gender-responsive extension support, encouraging their participation in technology development programs, and appropriate rainwater management would all contribute to harnessing the full potential of improved chickpea cultivars in Ethiopia.